PENGARUH MOTIVASI KERJA TERHADAP KINERJA GURU DENGAN DIMODERASI BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL (Studi Pada Guru SD Di Dabin V Kecamatan Ulujami Kabupaten Pemalang) - Bejo Utomo, 1352020064; Suhari, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study examines the effect of organizational culture and leadership style transformational role moderating influence on the performance of teachers work motivation. Population and sample is an elementary school teacher in Dabin V Ulujami the District Pemalang. From a population of 136 teachers, all members of the population used as a sample with saturated sampling technique. The research data is primary data obtained directly from the respondents to the questionnaire. The research method using SPSS for Windows version 21. The method of data analysis using Moderation Regression Analysis (MRA) type quasi moderator. From the test data and analysis conducted this study provide empirical evidence as follows: (1) work motivation positive effect on teacher performance; (2) Cultural organizations do not affect the performance of teachers; (3) The positive effect of transformational leadership style on teacher performance; (4) strengthen the influence of organizational culture motivation to work on teacher performance: (5) transformational leadership style weaken the influence of motivation to work on teacher performance. Theoretical implications, and recommendations for future research are also discussed in the final part in this study.Keywords: Work Motivation, Organizational Culture, Transformational Leadership Style and Performance Teachers